Complicaciones maternas en adolescentes y adultas afiliadas al régimen subsidiado, 2012 (2015)
ABSTRACT: The intervention of maternal complications and the minimization of its impact on mother and child health is a priority for this population's health care. Identifying factors associated with maternal complications is critical to devising policies and intervention strategies against this problem. Objective: to determine the factors associated with complications during the third trimester of pregnancy, delivery and puerperium of the mothers belonging to the subsidized health regime who receive care in a second level health care providing institution in Medellin. Methodology: an ambispective study whose exposure factors are age (exposed: adolescents aged 14 to 19, non-exposed:individuals aged 20 to 34) and maternal complications. Absolute and relative frequencies were calculated for the qualitative variables. Likewise, the mean, median and interquartile range were calculated for the quantitative variables. Moreover, the ratio of incidence was calculated for the complications along with the crude relative risk and the risk adjusted for confounding variables. Results: the main risk factor associated with maternal complications was inadequate prenatal care (Kessner criterion). In addition, attendance to the psychoprophilactic course was found to be a protecting factor. Conclusion: No significant differences were found between adolescents and adults. However, social (family relations), educational and health care aspects were found which may affect the health of the mothers belonging to the subsidized regime who receive health care in a second level institution in Medellin.